Successful closure of gastrocolic fistula using preoperative localization with charcoal nanoparticles tattooing - Lin, Nan; Cai, Zhicong; Yang, Weijin; Zhou, Youxu; Wang, Yu (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Lin N, Cai Z, Yang W, Zhou Y, Wang Y. Successful closure of gastrocolic fistula using preoperative localization with charcoal nanoparticles tattooing. Turk J Gastroenterol 2018; 29: 252-3.